Epicardial fat volume improves prediction of adverse clinical events. (4th February 2022) - Viegas, JM; Mano, TB; Reis, JP; Ramos, R; Fiarresga, A; Cacela, D; Marques, H; Figueiredo, L; Ferreira, RC
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Recent studies have demonstrated the potential of epicardial fat volume (EFV) to predict obstructive coronary artery disease (CAD), however its impact in clinical outcomes remains elusive. Objectives: To assess the association between EFV and demographic and morphometric data, coronary atherosclerotic burden and adverse events in a population of patients (pts) referred for coronary computed tomography angiography (CTA). Methods: Retrospective analysis of pts without known CAD referred for coronary CTA in a single tertiary care centre. A standardized protocol for quantification of EFV, thoracic fat volume (TFV), coronary artery calcification (CAC) and coronary angiography was performed. Endpoint was composite of cardiovascular death, nonfatal myocardial infarction and urgent hospitalization leading to revascularization at 12 months. Results: 72 pts were included, 58% male, mean age 67 ± 9 years. The prevalence of hypertension, dyslipidemia and diabetes was 75%, 82% and 24%, respectively. Median EFV was 101 (68) ml and total TFV 1504 (694) ml. EFV was directly related with age (rs= 0.42, p <0.001), male sex (135 ± 50 vs 78 ± 30, p <0.001), body mass index (rs= 0.32, p= 0.008) and TFV (rs= 0.27, p= 0.025). A positive correlation with CAC (rs= 0.47, p <0.001) and a significant association with CAD (116 ± 50 vs 90 ± 37, p= 0.029) and obstructive CAD (141 ± 60 vs 97 ± 39, p= 0.031) were demonstrated. Composite endpoint was observed in 13 pts (18%). After adjusting for all considered confounders, EFV remained an independent predictor of adverse events (OR: 1.015, 95%CI: 1.003-1.027, p= 0.041). ROC analysis of EFV (AUC 0.751, p = 0.005) allowed to estimate that EFV >124 ml had a sensibility and specificity to predict clinical outcomes of 69% and 71%, respectively. Conclusion: EFV positively relates to coronary atherosclerotic burden. This study also advocates that EFV may improve risk stratification for clinical outcomes. Larger studies are required to evaluate these results.